On Kamisar, Killing, and the Future of Physician-Assisted Death - Cantor, Norman L. (2004)
Tens - perhaps hundreds - of thousands of trees could have been spared over the last forty-five years had opponents of physician-assisted death only been content to let Yale Kamisar be their exclusive spokesperson. Their movement would have lost no significant substance or persuasive force, for Kamisar's 1958 article - Some Non-Religious Views Against Proposed 'Mercy-Killing' Legislation - presaged the shape and content of the subsequent forty-five year debate over legalizing physician-assisted death ( PAD ). Kamisar's article preceded by years the development of a whole jurisprudence relating to the withholding/withdrawing of life-sustaining medical treatment ( LSMT ) and the administration of pain-relief substances alleviating physical suffering while risking accelerated death. That article demonstrated remarkable prescience and intellectual honesty while shaping the content of opposition to PAD. Kamisar continued to participate in the debate for decades thereafter, always exhibiting remarkable intellectual honesty and insight. Kamisar's special insights started with his prediction about the legal status of a physician's withholding of LSMT. Years before cases addressing this issue emerged, he correctly anticipated that a physician's failure to provide LSMT might be treated as homicide by omission in light of a physician's affirmative fiduciary duty to the patient. He also foresaw that the fiduciary obligation would not rigidly dictate maintenance of medical life support in the face of a competent patient's request to withhold or withdraw LSMT. Later, he correctly forecast that the Supreme Court would refuse to find assistance in suicide to be a fundamental liberty and would instead leave regulation of physician-assisted suicide ( PAS ) to the states